ENDOSCOPIC FINDINGS IN DYSPEPSIA PATIENTS AT A RURAL TEACHING HOSPITAL- A RETROSPECTIVE STUDY. - Sanatan Behera; Arupam Mahapatro (Student's Journal of Health Research, 2023)
Background: Dyspepsia is a prevalent problem in India and around the world. Of the stomach and oesophagus, benign causes predominate, with occasional incidences of carcinoma. The presence of warning signs helps to indicate the presence of these carcinomas, though the utility of these warning signs has been questioned by various studies. Methods: Patients presenting with dyspepsia were examined with a gastroscope to determine the Cuttack region's etiological pattern and the utility of warning signs. This investigation included the first 100 patients at our institution to undergo upper gastrointestinal endoscopy for dyspepsia evaluation. Results: Despite exhibiting symptoms indicative of functional dyspepsia, the majority of patients (53%) exhibited unremarkable findings on visual examination. The most prevalent warning sign was weight loss, which had only a 4% predictive value. 10% of the patients had Malena, with a 30% positive predictive value. Conclusion: Significant weight loss as a warning sign to screen patients for gastrointestinal pathology appears inappropriate in rural settings.